Pengaruh Lingkungan Kerja Dan Supervisi Akademik Kepala Madrasah Terhadap Kinerja Guru - Sohabatul Aslamiyah; Ajang Muhammad Abdul Jalil (Journal on Education, 2024)
This research aims to determine the effect of the work environment and academic supervision of madrasah heads simultaneously have on teacher performance. This research uses a quantitative experimental method in the form of ex-post facto. The population and sample used a total sampling technique, namely all teachers at Madrasah Aliyah Negeri 2 Tasikmalaya with all respondents totaling 96 teachers. The data collection technique uses a questionnaire and to complete the questionnaire data, researchers also carry out observations, documentation and interviews. The data analysis technique in this research uses multiple regression analysis. The results of this research show: The work environment and academic supervision of madrasah principals have a positive and significant effect on teacher performance, this is evidenced by the linear equation Y = 18.078 + 0.488+ 1.267 and F count 137.422, with P-value or Sig 0.000 <0.05, thus is accepted and is rejected. With the coefficient of determination, the value of Adjusted R Square is 74.2%, which means that there is an influence of X1, X2 → Y of 74.2%. So it can be concluded that there is a simultaneous influence of the work environment and academic supervision of madrasah heads on teacher performance.